DATA MINING APPROACH TO DETECT ABUSIVE WORDS IN SOCIAL MEDIA. - NAGENDRAN, K.; BALAJI, S. M. AJIT; CHANTHRIKA, P. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
with the explosive growth of social media, online community has acquired an indisputable importance in today's society. Strong social effect occurs with high impact of interpersonal communications. The degree of anonymity from internet makes the online communities often invoked with abusive behaviors of some users. The degree of abuse varies on community but the user words and actions should not affect others like religion, race based etc. Abusive behaviors of users must be taken care by community maintainers and it is needed to take action on them. The communities are collapsed by these abusive behaviors. Inside community it may trigger legal issues and make the community members to leave from that community when unwanted or abusive messages are posted by the sender. Our proposed work display the alert message by showing it was an unwanted message and block the message at the sender side. Our system completely disregards message content for automatic abuse detection to ensure the privacy among users.